The Indian Textile Industry in Post Quota Era with Reference to Bangladesh - Singh, Gaganjot; Kumar Sarva, Mahesh; Gupta, Nitin (International Journal of Psychosocial Rehabilitation, 2020)
The textile industry has a prodigious presence in the Indian economy. In aspects of its contribution to GDP, job creation, and export earnings, it plays a significant role in shaping the growth trend of the Indian economy. During 1970-2004, a very famous trade instrument that is known as MFA was imposed by the European Union and other developed countries. The Multi-Fiber Arrangement was to allow time for the adjustment of developed countries to competition from developing countries, which could manufacture the same textile goods far cheaper. It heavily regulated the textile industry. Since the complete limitation of the MFA, many folds have risen in competition, with some developing countries like Vietnam & Bangladesh being strong, while some others, including the Philippines & Mexico, struggle to face up to this challenge. This study will address the effect on the Indian textile industry of this trade arrangement. It analyzes the dynamics that enhance industry’s export performance in the post‐MFA period. To review the impact of post quota era on Indian textile sector The Trade Intensity Index was used to determine the bilateral trade flow between India and Bangladesh in the post-quota era. The results show that the most important factors that contributed to competitiveness in exports of apparel over the period after the MFA include cheap labor, size of company, prices, foreign ownership, local raw material availability, the manufacture of new products, preferred working conditions, and market access. The following observations offer policymakers and business managers fresh insights into designing and implementing suitable policies to make textile exports competitive.